The multiple antibiotic resistance operon of enteric bacteria controls DNA repair and outer membrane integrity. Issue 1 (December 2017) - Sharma, Prateek; Haycocks, James; Middlemiss, Alistair; Kettles, Rachel; Sellars, Laura; Ricci, Vito; Piddock, Laura; Grainger, David
Abstract The multiple antibiotic resistance (mar ) operon ofEscherichia coli is a paradigm for chromosomally encoded antibiotic resistance in enteric bacteria. The locus is recognised for its ability to modulate efflux pump and porin expression via two encoded transcription factors, MarR and MarA. Here we map binding of these regulators across theE .coli genome and identify an extensivemar regulon. Most notably, MarA activates expression of genes required for DNA repair and lipid trafficking. Consequently, themar locus reduces quinolone-induced DNA damage and the ability of tetracyclines to traverse the outer membrane. These previously unrecognisedmar pathways reside within a core regulon, shared by most enteric bacteria. Hence, we provide a framework for understanding multidrug resistance, mediated by analogous systems, across the Enterobacteriaceae. Transcription factors MarR and MarA confer multidrug resistance in enteric bacteria by modulating efflux pump and porin expression. Here, Sharma et al. show that MarA also upregulates genes required for lipid trafficking and DNA repair, thus reducing antibiotic entry and quinolone-induced DNA damage. Transcription factors MarR and MarA confer multidrug resistance in enteric bacteria by modulating efflux pump and porin expression. Here, Sharma et al. show that MarA also upregulates genes required for lipid trafficking and DNA repair, thus reducing antibiotic entry and quinolone-induced DNA damage.